On Topological Indices of Fractal and Cayley Tree Type Dendrimers - Muhammad Imran; Abdul Qudair Baig; Waqas Khalid (Discrete Dynamics in Nature and Society)
The topological descriptors are the numerical invariants associated with a chemical graph and are helpful in predicting their bioactivity and physiochemical properties. These descriptors are studied and used in mathematical chemistry, medicines, and drugs designs and in other areas of applied sciences. In this paper, we study the two chemical trees, namely, the fractal tree and Cayley tree. We also compute their topological indices based on degree concept. These indices include atom bond connectivity index, geometric arithmetic index and their fourth and fifth versions, Sanskruti index, augmented Zagreb index, first and second Zagreb indices, and general Randic index for α={-1,1,1/2,-1/2}. Furthermore, we give closed analytical results of these indices for fractal trees and Cayley trees.